Direito concursal transfronteiriço: perspectivas para a superação da diversidade jurídica - Daniel Silva Queiroga (2018)
For more than 700 years, the subject of cross-border insolvency law has been on the agenda of doctrine and jurisprudence. In Brazil, the absence of express regulations regarding cross-border insolvency of business organizations brings challenges to the law, raising questions about international jurisdiction, active legitimacy, treatment of creditors, the right to be applied, conflict between public order rules of different States, among other possibilities. The purpose of this thesis is to analyze current ways of solving problems of cross-border insolvency law, in particular, how Brazilian law regulates the matter, as well as possible harmonization, uniformity or legislative unification on the subject. The analysis of the legal institute of cross-border insolvency law is done through the study of specialized doctrines to present the state of art, identifying how the main theoretical models (universalism and territorialism) and their cardinal derivations (cooperative territorialism, modified universalism, secondary insolvency, contractualism of corporate charter and international regime) answer the questions that guide the thesis. Following this, a study is carried out on ways of overcoming legal diversity and its implications for business law, pointing to the flow of harmonization, standardization or legislative unification. It also inquires how international law (public and private), community and integration law and international cooperation can contribute to the discussion of the topic. Existing international initiatives (universal, regional, community and integration) are sought in normative contact points that provide solutions regarding cross-border insolvency and how they can contribute to the evolution of Brazilian law. Thus, the way of the treaties and initiatives that were formulated between the 14th and 21st centuries marked by the struggle between unity and plurality, as well as between universalism and territorialism, is traversed. The study of UNCITRAL's Model Law on Cross-border Insolvency is relevant in view of the fact that it is the legislative measure most applied in the world, as well as the norms produced under EU law (EU and OHADA), which provide predictability of conduct and the possibility of interpretation coordinated by community courts. Furthermore, the initiatives of the American continent at the end of the twentieth century, which are in disuse and under review by the OAS due to the evolution of business law, are discussed. It also addresses the Brazilian legislation, historical and current, and its jurisprudential interpretation, in order to discuss the proposals to change national cross-border insolvency law, pointing out the need to reform or not Brazilian legislation.